The Role of Microbiota in Infant Health: From Early Life to Adulthood - Yao, Yao; Cai, Xiaoyu; Ye, Yiqing; Wang, Fengmei; Chen, Fengying; Zheng, Caihong (Frontiers in Immunology, 2021)
From early life to adulthood, the microbiota play a crucial role in the health of the infant. The microbiota in early life are not only a key regulator of infant health, but also associated with long-term health. Pregnancy to early life is the golden time for the establishment of the infant microbiota, which is affected by both environmental and genetic factors. Recently, there is an explosion of the studies on the role of microbiota in human diseases, but the application to disease or health is relatively limited because many aspects of human microbiota remain controversial, especially about the infant microbiota. Therefore, a critical and conclusive review is necessary to understand fully the relationship between the microbiota and the health of infant. In this article, we introduce in detail the role of microbiota in the infant from pregnancy to early life to long-term health. The main contents of this article include the relationship between the maternal microbiota and adverse pregnancy outcomes, the establishment of the neonatal microbiota during perinatal period and early life, the composition of the infant gut microbiota, the prediction of the microbiota for long-term health, and the future study directions of microbiota.